The use of personal listening log in a language classroom – A look at students’ feedback / Lim Teck Heng … [et al.] - Lim, Teck Heng; Marimuthu, Rasaya; Liaw, Shun Chone; Er, Ann Nah; Hoe, Foo Terng (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
In its effort to address the declining language proficiency among the undergraduates, the Academy of Language Studies at UiTM has decided to implement the Personal Listening Log – a variant of journal writing in which students record their responses to listening exercises. In the Personal Listening Log, which is done outside the formal language class, students need to respond, predict and/or reflect on the given listening texts. The use of the Personal Listening Log is believed to increase students’ knowledge, vocabulary and also their listening skills. The data is obtained via a survey questionnaire, which is administered to a group of 36 first-year students, as well as interviews with ten students. The findings are discussed in terms of a) the problems that students face in carrying out the activity; and b) the students’ responses to the activity. Based on students’ feedback that was obtained, the paper concludes with some recommendations for language instructors who are contemplating on using the Personal Listening Log to enhance students’ interest in listening to materials in English as well as listening proficiency